Family Study of Different Hemoglobin Disorders and Variants in North-Western India in Tertiary Center - Neha Garg; Chetan Jain; Karandeep Singh; Aditi Bagla (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Hemoglobin-related disorders are among the most common inherited genetic disorders in the world. They are posing a serious health burden to the global health system. As per WHO, the highest incidence of hemoglobinopathies is in the Middle East and Indian subcontinent. Screening methods like High-Performance Liquid Chromatography (HPLC) help in determining values of HbA, HbA2, and HbF and diagnosing hemoglobinopathies at the initial stages. The present study aims to determine the role of family studies using HPLC in hemoglobin-related disorders. A retrospective study of 48 months between January 2019 and January 2024, comprising 137 patients was conducted. Patients attending the Outpatient Department (OPD)and admitted to the Inpatient Department (IPD) with anemia and abnormal values of different hemoglobin (HbA, HbA2, HbF, etc.) along with family members were included in this study. Patients with less than 3 months of history of blood transfusion and less than 6 months of age were excluded from the study. A total number of 572 patients with Hb < 11 g/dL were screened. Out of 153 (26.74%) patients, 137 (23.95%) patients and their family members agreed to the family study. Among 137 patients, 72 were females and 65 were males. Therefore M:F ratio was 0.90:1. Pallor was present in 121 (88.32%) cases and splenomegaly was seen in 49 cases (35.76%). HPLC along with family studies is a quick and minimally invasive method to screen high to medium-risk large communities, which in return helps in controlling the spread of clinically dreadful homozygous state of hemoglobin disorders.